Effect of ethnicity on care pathway and outcomes in patients hospitalized with influenza A(H1N1)pdm09 in the UK - Nyland, G.A.; McKenzie, B.C.; Myles, Puja R.; Semple, M.G.; Lim, W.S.; Openshaw, Peter J.M.; Read, R.C.; Taylor, B.L.; Brett, S.J.; Mcmenamin, J.; Enstone, J.E.; Bannister, B.; et al. (Cambridge University Press, 2014)
Data were extracted from the case records of UK patients admitted with laboratory-confirmed influenza A(H1N1)pdm09. White and non-White patients were characterized by age, sex, socioeconomic status, pandemic wave and indicators of pre-morbid health status. Logistic regression examined differences by ethnicity in patient characteristics, care pathway and clinical outcomes; multivariable models controlled for potential confounders. Whites (n = 630) and non-Whites (n = 510) differed by age, socioeconomic status, pandemic wave of admission, pregnancy, recorded obesity, previous and current smoking, and presence of chronic obstructive pulmonary disease. After adjustment for a priori confounders non-Whites were less likely to have received pre-admission antibiotics [adjusted odds ratio (aOR) 0·43, 95% confidence interval (CI) 0·28–0·68, P < 0·001) but more likely to receive antiviral drugs as in-patients (aOR 1·53, 95% CI 1·08–2·18, P = 0·018). However, there were no significant differences by ethnicity in delayed admission, severity at presentation for admission, or likelihood of severe outcome.